ANALISIS KUALITAS PELAYANAN DAN KEPUASAN ANGGOTA KOPERASI SIMPAN PINJAM USAHA BERSAMA DI TEMBILAHAN - Ulfa Zuliana Z; Gusnardi '; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The purpose of this study was to determine the service quality andmember satisfaction of Koperasi Simpan Pinjam Usaha Bersama Tembilahan. Thepopulation in this study are members of Koperasi Simpan Pinjam Usaha BersamaTembilahan. Research using the quadrant method (Importance Performance Analysis).Data were analyzed using quantitative descriptive analysis. The study states that theaverage score of expectations assessed on five (5) indicator that is tangible, reliability,responsiveness, assurance and empathy is of 3.52 means that the level of expectations ofcooperative members with the services category Important average score performanceis assessed by 5 (five) indicator that is tangible, reliability, responsiveness, assuranceand empathy is at 2.64 meaning that the level of expectation of cooperative members toservices is satisfied. But the score is lower than the scores of expectations. Based oncalculations, the degree of correspondence between expectations and performance ofservices in the Koperasi Simpan Pinjam Usaha Bersama Tembilahan lies in the range of60% - 81% were categorized Satisfied. The results of Cartesian matrix analysis diagramshows that tangible, reliability and responsiveness is a variable which is a priority ofthe cooperative and based on the assessment of performance, these three variablescategory should be maintained. Assurance and empathy in terms of the level ofexpectation in the category less than expected while terms of level of performance isconsidered excessive that needs to be reduced, especially in terms of relations betweenemployees and members of Koperasi Simpan Pinjam Usaha Bersama Tembilahan.Keyword: Service Quality dan Satisfaction2